Post-infection symptoms following two large waterborne outbreaks of Cryptosporidium hominis in Northern Sweden, 2010–2011 - Rehn, Moa (BMC Public Health, 2015)
BACKGROUND: In 2010–2011, two large waterborne outbreaks caused by Cryptosporidium hominis affected two cities in Sweden, Östersund and Skellefteå. We investigated potential post-infection health consequences in people who had reported symptoms compatible with cryptosporidiosis during the outbreaks using questionnaires. METHODS: We compared cases linked to these outbreaks with non-cases in terms of symptoms present up to eleven months after the initial infection. We examined if cases were more likely to report a list of symptoms at follow-up than non-cases, calculating odds ratios (OR) and 95 % confidence intervals (CI) obtained through logistic regression. RESULTS: A total of 872 (310 cases) and 743 (149 cases) individuals responded to the follow-up questionnaires in Östersund and Skellefteå respectively. Outbreak cases were more likely to report diarrhea (Östersund OR: 3.3, CI: 2.0-5.3. Skellefteå OR: 3.6, CI: 2.0-6.6), watery diarrhea (Östersund OR: 3.4, CI: 1.9-6.3. Skellefteå OR: 2.8, CI: 1.5-5.1) abdominal pain (Östersund OR: 2.1, CI: 1.4-3.3, Skellefteå OR: 2.7, CI: 1.5-4.6) and joint pain (Östersund OR: 2.0, CI: 1.2-3.3, Skellefteå OR: 2.0, CI: 1.1-3.6) at follow-up compared to non-cases. CONCLUSIONS: Our findings suggest that gastrointestinal- and joint symptoms can persist several months after the initial infection with Cryptosporidium and should be regarded as a potential cause of unexplained symptoms in people who have suffered from the infection. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12889-015-1871-6) contains supplementary material, which is available to authorized users.